Effect of deposition parameters on microstructure and tribological properties of hard CA-PVD multi-component TiAlCrN and TiAlCrCN coatings - Misiruk, I.O.; Tymoshenko, A.I.; Taran, V.S.; Taran, A.V.; Romaniuk, S.P.; Skoblo, T.S.; Maltsev, T.V.; Plutargaev, A.V.; Deryabkina, E.S. (Вопросы атомной науки и техники, 2020)
Multicomponent TiAlCrN and TiAlCrCN coatings were deposited using vacuum arc evaporation technique on AISI 430 stainless steel. The influence of working gas pressure, C ⁄ N ratio, bias voltage on the structure and tribomechanical properties of the obtained coatings has been studied. The surface morphology, chemical compound of the coatings obtained under the various conditions has been analyzed by SEM with EDX, XRD, and XRF analysis. The dry wear pad-on-disc tests against 100Cr6 counterbody at 20 N load have been carried out. It was established that Vickers micro-hardness was varied from 26 to 41 GPa depending on deposition parameters.